153k views
1 vote
What if the simplest form of the radical expression?

What if the simplest form of the radical expression?-example-1
User HypeWolf
by
6.2k points

1 Answer

3 votes

Answer:


\large\boxed{(\sqrt2+\sqrt5)/(\sqrt2-\sqrt5)=-(7+2√(10))/(3)}

Explanation:


\text{Use}\ (a-b)(a+b)=a^2-b^2\ \text{and}\ (a+b)^2=a^2+2ab+b^2\\\\\\(\sqrt2+\sqrt5)/(\sqrt2-\sqrt5)=(\sqrt2+\sqrt5)/(\sqrt2-\sqrt5)\cdot(\sqrt2+\sqrt5)/(\sqrt2+\sqrt5)=((\sqrt2+\sqrt5)^2)/((\sqrt2)^2-(\sqrt5)^2)\\\\=((\sqrt2)^2+2(\sqrt2)(\sqrt5)+(\sqrt5)^2)/(2-5)=(2+2√((2)(5))+5)/(-3)\\\\=-(7+2√(10))/(3)

User Sha
by
6.1k points